Advances in the care of breast cancer survivors - Cathcart-Rake, Elizabeth J; Tevaarwerk, Amye J; Haddad, Tufia C; D’Andre, Stacy D; Ruddy, Kathryn J (BMJ. British medical journal (Clinical research ed.), 2023)
Breast cancer survivors may experience significant after effects from diagnoses of breast cancer and cancer directed therapies. This review synthesizes the evidence about optimal management of the sequelae of a diagnosis of breast cancer. It describes the side effects of chemotherapy and endocrine therapy and evidence based strategies for management of such effects, with particular attention to effects of therapies with curative intent. It includes strategies to promote health and wellness among breast cancer survivors, along with data to support the use of integrative oncology strategies. In addition, this review examines models of survivorship care and ways in which digital tools may facilitate communication between clinicians and patients. The strategies outlined in this review are paramount to supporting breast cancer survivors’ quality of life.